Neurocognitive impairments in patients with schizophrenia and schizophrenia spectrum disorders: cluster analysis results - M. V. Karyakina; A. B. Shmukler (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2020)
There are results of cluster analysis of neurocognitive impairments in 85 patients with schizophrenia spectrum disorders in the article. Three patient groups were discriminated based on the results. These groups differ from each other both by severity of general cognitive impairment and by severity of impairments of the specific cognitive functions. There are differences between groups by specific demographic and clinical parameters. However sensitivity analysis does not find influence of these clinical parameters on the cognitive differences between groups, which stay certain after symptoms are taken into account.